Dental trauma: evaluation of the conduct of Dental surgeons who work in the municipal dental emergency room (Research, Society and Development, 2021)
The aim of this study was to evaluate the behavior and knowledge of dental surgeons who work in the municipal dental emergency room, regarding the proposal for treating periodontal ligament damage after dental trauma. This is a descriptive work with a quantitative approach. A cross-sectional observational study was carried out, with the application of an electronic questionnaire, which consisted of nine questions related to the professional profile and performance in the face of periodontal ligament damage caused by dental trauma, except for avulsion, validated by Pedrini in 2008 and adapted for the Google Forms platform. It can be seen in this work, after analyzing the data, that among those surveyed, most were male, all over 50 years old, with approximately 30 years of graduation and predominantly trained in a private university. As for specialization, 75.0% of professionals are specialists. Regarding the dentist's conduct, whether it is adequate or inadequate in the treatment of dental trauma, it can be concluded that in concussion (50.0%) it was inadequate and (50.0%) adequate, in subluxation it was 100% inadequate, in the extrusive dislocation (50.0%) it was inadequate and (50.0%) adequate, lateral dislocation was 100% adequate and intrusive dislocation (75.0%) was inadequate and (25.0%) adequate. Therefore, it was found that dental surgeons do not have enough knowledge to act appropriately to the damage caused to the periodontal ligament after dental trauma.